A Sugarcane G-Protein-Coupled Receptor, ShGPCR1, Confers Tolerance to Multiple Abiotic Stresses - Ramasamy, Manikandan; Damaj, Mona B.; Vargas-Bautista, Carol; Mora, Victoria; Liu, Jiaxing; Padilla, Carmen S.; Irigoyen, Sonia; Saini, Tripti; Sahoo, Nirakar; DaSilva, Jorge A.; Mandadi, Kranthi K. (Frontiers in Plant Science, 2021)
Sugarcane (Saccharum spp.) is a prominent source of sugar and serves as bioenergy/biomass feedstock globally. Multiple biotic and abiotic stresses, including drought, salinity, and cold, adversely affect sugarcane yield. G-protein-coupled receptors (GPCRs) are components of G-protein-mediated signaling affecting plant growth, development, and stress responses. Here, we identified a GPCR-like protein (ShGPCR1) from sugarcane and energy cane (Saccharum spp. hybrids) and characterized its function in conferring tolerance to multiple abiotic stresses. ShGPCR1 protein sequence contained nine predicted transmembrane domains connected by four extracellular and four intracellular loops, which could interact with various ligands and heterotrimeric G-proteins in the cells. ShGPCR1 sequence displayed other signature features of a GPCR such as a putative GTP-binding domain, as well as multiple myristoylation and protein phosphorylation sites, presumably important for its biochemical function. Expression of ShGPCR1 was upregulated by drought, salinity, and cold stresses. Subcellular imaging and calcium (Ca2+) measurements revealed that ShGPCR1 predominantly localized to the plasma membrane and enhanced intracellular Ca2+ levels in response to GTP, respectively. Furthermore, constitutive overexpression of ShGPCR1 in sugarcane conferred tolerance to the three stressors. The stress tolerance phenotype of the transgenic lines corresponded with activation of multiple drought-, salinity-, and cold stress marker genes such as Saccharum spp. LATE EMBRYOGENESIS ABUNDANT, DEHYDRIN, DROUGHT RESPONSIVE 4, GALACTINOL SYNTHASE, ETHYLENE RESPONSIVE FACTOR 3, SALT OVERLY SENSITIVE 1, VACUOLAR Na+/H+ ANTIPORTER 1, NAM/ATAF1/2/CUC2, COLD RESPONSIVE FACTOR 2, and ALCOHOL DEHYDROGENASE 3. We suggest that ShGPCR1 plays a key role in conferring tolerance to multiple abiotic stresses and the engineered lines may be useful to enhance sugarcane production in marginal environments with fewer resources.